2010
DOI: 10.1007/s12646-010-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Substance Abuse in a Sample of Nigerian Undergraduate Students: The Role of Core Self-evaluations and Delay of Gratification

Abstract: Documented empirical evidence indicates that substance abuse among young people, especially students, is assuming an unprecedented upward surge worldwide. Substance abuse among students is associated with a myriad of negative physical, social and psychological consequences, including liver, cranial, and cardiovascular diseases, cancers, vehicular fatalities, mental and behaviour disorders, violence, declining grades, increased potential for dropout and high truancy rates, suicides, homicides, and accidental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…This finding of the present study lend support to earlier positions researchers (3,5,8,10,14,27), who reported that male students were, by far, more likely than their female counterparts to abuse substances and justify such behaviour as a means of coping with the stresses and challenges of school work. Additionally, cultural factors may also explain why males abuse substances more than females.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding of the present study lend support to earlier positions researchers (3,5,8,10,14,27), who reported that male students were, by far, more likely than their female counterparts to abuse substances and justify such behaviour as a means of coping with the stresses and challenges of school work. Additionally, cultural factors may also explain why males abuse substances more than females.…”
Section: Discussionsupporting
confidence: 91%
“…As noted by (14), younger students may not be as capable of exerting control over their substance use behaviours as their colleagues who are "more mature". Moreover, it is quite possible that the excitement of leaving home/parents for a "freer environment" might be too much for the younger students to control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Canadian Center on Substance Abuse (2010), for instance, reported that Canadian undergraduate students were more than three time as likely to engage in weekly risky drinking as the general population. Abikoye and Adekoya (2010) found that about one-thirds of the respondents in their study (Nigerian university students) reported hazardous drinking patterns. It has been reported that 40% of undergraduates engaged in heavy drinking (Johnston et al 2006) and that college students had more occasions of heavy drinking within the past 30 days than non-college students of the same age (Johnston et al 2006).…”
Section: Introductionmentioning
confidence: 80%
“…Why alcohol is a sensitive issue in Nigeria, is because young people and women are culturally restrained from alcohol consumption in many communities. For example, they were excluded from alcohol consumption in the traditional epoch due to sociocultural or religious constraints (Odejide et al 1987), but in contemporary Nigeria, this group is drinking hazardously with diverse frightening motives (Abikoye and Adekoya 2010;Chikere and Mayowa 2011;Abayomi et al 2013). Because of this paradigm shift in alcohol consumption among young people and women in Nigeria, many alcohol-related problems that hitherto did not exist between 1960 and 1990s are extant in contemporary Nigeria, and many of these phenomena may not be properly addressed with a single method, especially ''quantitative fixed-choice'' design that often fails to capture the social theme of any inquiry (Silverman 2011, p.166).…”
Section: Discussion and Conclusion The Necessities Of Mixed Methods Dmentioning
confidence: 99%